2015
DOI: 10.4085/1062-6050-49.3.90
|View full text |Cite
|
Sign up to set email alerts
|

High-Intensity Running and Plantar-Flexor Fatigability and Plantar-Pressure Distribution in Adolescent Runners

Abstract: Fatigue resistance in the plantar flexors declined after a high-intensity running bout performed by adolescent male distance runners. This phenomenon was associated with increased loading under the medial arch in the fatigued state but without any excessive pronation.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
31
0

Year Published

2016
2016
2025
2025

Publication Types

Select...
8
2

Relationship

2
8

Authors

Journals

citations
Cited by 43 publications
(34 citation statements)
references
References 37 publications
3
31
0
Order By: Relevance
“…Considering that human anthropometry is subject to a circadian rhythm (eg, larger body length in the morning than in the evening), 18 it is hypothesized that the foot is exposed to physical load throughout the day that might have an effect on the MLA. This is supported by Fourchet et al, 19 who showed changes in measured pedobarographic foot characteristics following high-intensity running.…”
supporting
confidence: 63%
“…Considering that human anthropometry is subject to a circadian rhythm (eg, larger body length in the morning than in the evening), 18 it is hypothesized that the foot is exposed to physical load throughout the day that might have an effect on the MLA. This is supported by Fourchet et al, 19 who showed changes in measured pedobarographic foot characteristics following high-intensity running.…”
supporting
confidence: 63%
“… 23) Foot pressure measurement is increasingly used for clinical and research purposes in diabetic foot ulcer, footwear or orthosis, foot deformities, and sports activities. 1 3 4 14 16 18 24 25 26 27) It is necessary to establish normal data according to sex and ethnic groups in order to help clinicians and researchers set appropriate treatment goals and obtain appropriate control data.…”
Section: Discussionmentioning
confidence: 99%
“…Fourchet et al showed that the total contact area of the foot would increase after fatigue due to increase in the contact area of the midfoot [27]. Nagel et al in their study on 200 subjects participating in a marathon race investigated the parameters of plantar pressure measurements.…”
Section: Discussionmentioning
confidence: 99%